The Effect of Workload and Work Stress On Auditor Job Satisfaction is Moderated by Organizational Support (Case Study at a Public Accounting Firm in Semarang) - Patricia Dhiana Paramita; Arditya Dian Andika; Heru Sri Wulan (Jurnal Akuntansi dan Pajak, 2023)
Public accountants in carrying out their duties must be carried out in a professional manner and comply with auditing standards and the professional code of ethics as stipulated. It takes high independence and integrity for an auditor in carrying out his profession. The initial survey that has been carried out has problems with decreasing auditor job satisfaction, which can affect their performance in carrying out their duties. Starting from the existence of these problems, the formulation of the research problem is how to increase auditor job satisfaction by managing the workload according to the auditor's ability and eliminating work stress moderated by support from the organization. This study aims to determine the impact of workload and work stress partially and simultaneously on job satisfaction, to find out whether organizational support weakens the impact of workload and work stress simultaneously on job satisfaction. A total of 104 people out of 140 auditors were taken as samples in this study, using the Proportional Purposive Sampling technique. The data analyzed came from distributing questionnaires to auditors working at the Public Accountant Firm that was sampled. The data analysis technique uses Moderated Regression Analysis (MRA). The results of the research can be described that workload and work stress partially and simultaneously have a significant positive impact on job satisfaction. In addition, organizational support weakens the impact of workload and work stress partially on job satisfaction. The policy that must be taken by the management of the Public Accounting Firm in Semarang is to provide work that is tailored to the skills and abilities of the auditors, trying to eliminate work stress and increasing support from the organization to the auditors in order to increase the job satisfaction of the auditors.